Thailand’s export and ASEAN economic integration: A gravity model with state space approach - Pathairat Pastpipatkul (2018)
© Springer International Publishing AG 2016. The purpose of this paper is to study bilateral behavior of trading partners of Thailand in AEC and capture advantageous characteristics of two-sided trades between them. Gravity model is commonly used for investigating bilateral trade. However, log linear transformation of gravity model could cause bias resulting in heteroscedasticity. Furthermore, one of the assumptions of OLS or panel estimators has to be homoscedasticity which leads to the inconsistency of parameter estimator. In the gravity model, coefficients are also assumed to be constant over time meanwhile it tends to be volatility in Thai export earnings. Hence constant coefficient of gravity model might not be adequate in explaining the behavior of Thailand’s export. As an alternative approach, state space approach with gravity model tends to be more appropriate. It does not only need no homogeneous assumption, but also determines the changes in the coefficients over time. Therefore the estimation from state space approach capture more characteristics of trade in each country and also provides more accurate parameter estimators.